The Influence of Agulhas Leakage on Primary Production and Nitrogen Cycling in the Southeastern Atlantic Ocean. Issue 9 (22nd September 2022) - Wallschuss, Sina; Mdutyana, Mhlangabezi; Parrott, Ruan G.; Forrer, Heather J.; Roman, Raymond; Walker, David R.; Ansorge, Isabelle J.; Fawcett, Sarah E.
Abstract: The well‐established importance of Agulhas Current "leakage" for Indian‐Atlantic Ocean exchange of heat and salt raises the question of the relevance of Agulhas eddies for carbon and nitrogen cycling. We measured net primary production (NPP), nitrate and ammonium uptake, and nitrification along a transect of the Cape Basin (CB) in winter 2017, including across an anticyclonic Agulhas eddy sampled at high‐resolution. Euphotic zone‐integrated rates of NPP and nitrogen uptake were more than three‐fold lower at the eddy center than at its edges, with intermediate rates measured outside the eddy. Additionally, proportionally more nitrate was consumed at the eddy edges than at its center. Mixed‐layer integrated nitrification rates were highest at the eddy‐center, with lower rates at the edges and in the surrounding basin. Accounting for phytoplankton consumption of newly nitrified nitrate in the eddy decreased the carbon export potential inferred from nitrate uptake (i.e., the f ‐ratio) by 66% ± 37% (vs. a 14% ± 22% decrease across the rest of the transect). At most stations, NPP and total measured nitrogen uptake were decoupled relative to stoichiometric expectations, with roughly a third of NPP possibly supported by regenerated dissolved organic nitrogen (DON). Accounting for DON uptake decreased the average f ‐ratio from 0.28 ± 0.26 to 0.22 ± 0.21, with the highest f ‐ratio estimated for an eddy‐edge station (0.64) and the lowest for its center (0.00). While the low productivity metrics measured in the eddy‐center could imply that Agulhas leakage decreases carbon export potential in the CB, enhanced nutrient supply and consumption at eddy edges may (partly) offset this reduction. Plain Language Summary: Mesoscale eddies are abundant in the ocean, transporting physical, chemical, and biological properties from the eddy source region. Eddies can also cause small‐scale upwelling and/or downwelling, which affect the local biogeochemistry and biology (e.g., altering phytoplankton growth by changing the nutrient and/or light conditions). Large anticyclonic eddies that pinch off the Agulhas Current south of Africa transfer warm, salty waters from the Indian to the Atlantic Ocean, thereby playing a crucial role in ocean circulation. By contrast, little is known of the role of Agulhas eddies in carbon and nitrogen cycling. We find that the physical perturbations caused by the passage of an Agulhas eddy into the southeastern Atlantic stimulate primary production and nitrate uptake at the eddy edges, implying enhanced CO2 removal to depth, while productivity (and CO2 removal) is depressed at the eddy center. Additionally, the deep mixed layers created by the eddy's anticyclonic circulation favor high rates of nitrification, which produces recycled nitrate. Phytoplankton consumption of this nitrate yields no net removal of CO2, exacerbating the dampening effect of the eddy on Atlantic productivity. It is possible, however, that the reduction in productivity may be partly offset by the elevated supply and consumption of subsurface nutrients at the eddy edges. Key Points: Primary production and carbon export potential are elevated at Agulhas eddy edges and reduced at their centers Agulhas eddies host high rates of mixed‐layer nitrification that can supply 100% of phytoplankton nitrate Dissolved organic nitrogen appears to fuel a significant fraction of primary production in Agulhas eddies and the Cape Basin